The relationship of self-efficacy sources and metacognitive reading strategies: Mediating role of reading self-efficacy beliefs - Shehzad, M. Waleed; Hamzah, Mohd Hilmi; Mohd Rawian, Rafizah (iRASD, 2018)
This research article presents a conceptual model of the proposed study involving a relationship between self-efficacy sources and metacognitive reading strategies by employing reading self-efficacy beliefs as a mediating variable. Initially, this paper provides a brief background of the variables involved in the study. Furthermore, it gives an insight into the problems faced by the Saudi Preparatory Year Programme (PYP) students regarding employing metacognitive reading strategies while reading. There are three main research objectives of the current study. Firstly, to determine the correlation between self-efficacy sources and self-efficacy beliefs. Secondly, to determine the correlation between self-efficacy beliefs and metacognitive reading strategies. Lastly, to determine the mediating role of selfefficacy beliefs between self-efficacy sources and metacognitive reading strategies. Additionally, three hypotheses are generated on the basis of the reviewed literature. Lastly, it is hoped that the findings of this study would be beneficial for the students, teachers, policy makers and syllabus designers.